IMPLEMENTING THE MULTIPLE INTELLIGENCES LEARNING MODEL TO ENHANCE ISLAMIC RELIGIOUS EDUCATION OUTCOMES FOR CHILDREN WITH SPECIAL NEEDS IN INCLUSIVE AND SPECIAL SCHOOLS IN MALANG, INDONESIA - Uma, Yuli Choirul; yasin, Ahmad Fatah; Wahyuni, Esa Nur (Universitas Islam Madura, 2025)
This study aims to describe the implementation of the Multiple Intelligences (MI) based learning model in improving the learning outcomes of Islamic Religious Education (PAI) for Children with Special Needs (ABK) at Saleh Children's Elementary School Malang and SLB Autisme River Kids. Using a qualitative approach with a case study type, data was collected through observation, interviews, and documentation with key informants including PAI teachers, principals, and parents. The results of the study show that the implementation of multiple intelligences (MI) is carried out by identifying the dominant intelligence of each student, then designing appropriate learning strategies, such as visual media, kinesthetic activities, and musicalization. This strategy increases motivation, participation, and understanding of Islamic values contextually and gradually. The success of the implementation is greatly influenced by the creativity of teachers, school support, and parental collaboration. This research shows that the MI approach has great potential to build an inclusive and equitable religious education system. The implication is that policies are needed that encourage differentiating curricula and teacher training that is responsive to the needs of ABK. In addition, synergy between schools, families, and communities needs to be strengthened to create an adaptive learning environment that respects the diversity of intelligence. These findings are an important contribution to the reform of PAI pedagogy in inclusive primary schools.